A preplanning method for stereotactic radiosurgery to improve treatment workflow. (8th May 2016) - Ahn, Kang‐Hyun; Ozturk, Naim; Smith, Brett; Slavin, Konstantin V.; Koshy, Matthew; Aydogan, Bulent
Abstract : Frame‐based stereotactic radiosurgery (SRS) requires fixation of an invasive head ring to ensure accurate targeting. Minimizing waiting time with a fixed head ring is important for patient comfort and satisfaction. We report a practical preplanning solution for the Brainlab iPlan treatment planning system that reduces waiting time by expediting the planning process on treatment day. A water‐filled anthropomorphic head phantom was used to acquire a surrogate CT image set for preplanning and fused with patient's MRI, which was obtained before the day of treatment. Once an acceptable preplan was obtained, it was saved as a plan template and the phantom image set was removed from the Brainlab database to prevent any confusion and mix‐up of image sets. On the treatment day, the patient's CT and MRI were fused, and the customized beam settings of the preplan template were then applied and optimized. Up to 10‐fold of reduction in treatment plan time was demonstrated by bench testing with multiple planners and a variety of cases. Loading the plan template and fine‐tuning the preconfigured beam settings took only a small fraction of the preplan time to restore the conformity and dose falloff comparable to those of the preplan. For instance, preplan time was 2 hr for a two‐isocenter case, whereas, it took less than 20 min for a less experienced planner to plan it on the day of treatment using the preplan method. The SRS preplanning technique implemented in this study for the Brainlab iPlan treatment planning system offers an opportunity to explore possible beam configurations thoroughly, optimize planning parameters, resolve gantry angle clearance issues, and communicate and address challenges with physicians before the treatment day. Preplanning has been proven to improve plan quality and to improve efficiency in our clinic, especially for multiple‐isocenter and dosimetrically challenging cases. PACS number(s): 87.53.Ly, 87.55.D‐, 87.55.Gh, 87.55.tm